The Potential of Negation Questions for Affecting the Audience in Dehkhoda's Amsal-o-Hekam - Ahmadipooranari, Zohre; Mousa Ghonchepour; Mohammadidahaj, Fatemeh (Funūn-i adabī, 2025)
The negation question is one of the rhetorical questions that are widely used in language and literature. Poets and writers use it according to the situation to persuade the audience. The application of negation questions in Dehkhoda's Amsal-o-Hekam is also noteworthy, as the majority of rhetorical questions in this book are of the negation question type. Moreover, negation questions have unique characteristics compared to other rhetorical questions. Given these two points, the present research answers the question of how negation questions are strengthened with expressive and semantic methods to have a greater impact on the audience. This descriptive-analytical research is of a library type. It utilizes the principles of rhetoric, semantics, and logic in some cases. As the evidence extracted from the book of Amsal-o-Hekam shows, negation questions have sufficient power to emphasize the negative sentence, because they are accompanied by expressive possibilities such as allegory, allusion, and theological method. On the other hand, the content of some negation questions in Amsal-o-Hekam includes the premises of the reasoning, especially accepted premises in logic (Maghbulat), testimony (Motavaterat), and generally accepted beliefs (Mashhurat), which is why they have a special persuasive power.